Pelvic floor symptoms in elite female rugby players: prevalence and impact on performance - Dakic, J.; Perraton, L.; Lindstrom, J.; Hain, E.; Chuah, S.; Stay, S. (Journal of Science and Medicine in Sport, 2024)
Introduction: Approximately 60% of female ball-sport athletes experience pelvic floor (PF) symptoms e.g. leaking urine. A prior study found 60% of Australian rugby players reported urinary incontinence (UI). Beyond UI, the prevalence and impact of other PF symptoms such as anal incontinence and pelvic pain in high-impact female sports, including rugby, remains largely unknown. Understanding PF symptom prevalence and impact can allow for targeted screening and management programs to be implemented. This study investigated the prevalence of PF symptoms and impact on performance in Australian female rugby players. Methods: A cross-sectional, observational study was conducted. Participants were Australian, elite, female, Super W and Rugby 7 players (n=56). Data was collected via written questionnaire by a Rugby Australia Doctor as part of player`s annual medical screening. Validated patient reported outcome measures on pelvic health established: the presence/severity of UI (ICIQ-UI SF), presence and bother of PF symptoms (PFBQ), presence of urinary tract infection, constipation, and voiding difficulty (APFQ). Purpose designed questions established symptom impact on performance and wellbeing. Data were analysed descriptively. Results: Participants were on average 22.4 years old (SD:5.9) and BMI 26.3 kg/m2 (SD:4.6) They had played on average 6.5 years of Rugby (SD:4.4) and 3.3 years (SD:2.3) at an elite level. The majority were nulliparous (94, n=53). More than half (57%, n=32) experienced PF symptoms during sport. Urinary incontinence was the most prevalent PF symptom (41%, n=23). Other PF symptoms experienced during sport included: anal incontinence (29%), bladder urgency (21%)/frequency (14%) and pelvic pain (12%). Approximately half (n=14) of those with symptoms, experienced them during competition. Symptoms were common during competition (44%), tackling (50%), jumping (31%), lifting weights (19%) and practising new skills (16%). One in two symptomatic players reported an impact on performance (53%). Impacts included: reduced training intensity (34%); activity avoidance e.g. jumping (25%) and loss of concentration (9%). One in three symptomatic players (34%) were either somewhat/moderately bothered by the impact on their performance. Players emptied their bladder before training (81%), restricted their fluid intake before (25%) or during competition (9%) and wore dark coloured clothing (19%) to avoid or manage symptoms. Discussion: One in two players reported PF symptoms during sport, most commonly UI, with the prevalence closely resembling prior studies in Australian and UK rugby union players. This is the first study to establish that anal incontinence, bladder urgency/frequency and pelvic pain are also prevalent in female Rugby players. One in two symptomatic players reported a negative impact of PF symptoms on performance, including reducing or changing training to avoid provoking symptoms. Elite female rugby players require assessment and management of pelvic floor symptoms to maximise training and performance Impact/Application to the field: • Over 50% of elite female rugby players reported pelvic floor symptoms during sport. One in two symptomatic players reported a negative impact on their performance including training limitations. • There is a need for targeted screening, education and management strategies to reduce symptoms and the impact on performance. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.